A prospective observational study of drug usage in the management of snake bite patients and their outcome in a tertiary care teaching hospital - Hirebail, Supriya Kumari; H., Nagabushan; G. M., Prakash (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The objectives of the study were to assess the pattern of management of snakebite especially with respect to use of anti- snake venom and other supportive treatment given and to assess the effect of anti-snake venom on different types of snakebite and to assess their outcome. Methods: A prospective observational study was conducted over a period of 6 months, after getting approval from Institutional Ethics committee. Total of 144 snake bite patients were analysed for six months duration for use of anti-snake venom and other supportive treatment in their management and were assessed for their outcome like recovery, morbidity and mortality. Results: Out of 144 snake bite patients analysed, 71.5% had poisonous type and 28.4% had non- poisonous type of snake bite. Among the total number of snakebites, 47.2% were unknown type and among the known type 25% were viper, 13.2% cobra, 7.6% krait, 6.3% sea snake and 0.7% green snake. Anti-snake venom (ASV) was given to 62 patients depending on severity, of which, 22 patients developed reaction to ASV. Patient with reaction to ASV were treated with corticosteroid and antihistamine injection. Morbidity was seen in 29.1% of patients who developed either cellulitis or gangrene of bitten area, which was more commonly seen among viper bite patients (54.7%). Conclusions: Snakebite is one of the commonest tropical diseases leading to envenomation and poisoning especially in rural areas of tropical countries which has to be treated as early as possible to prevent complications. Majority of the cases in our study were of viper bite and most of them have recovered after treatment.